2014
DOI: 10.1111/jns.12100
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of proximal strength training in Charcot‐Marie‐Tooth disease

Abstract: Gait analysis of people with Charcot-Marie-Tooth (CMT) disease revealed proximal adaptive gait strategies to compensate for foot drop. We previously demonstrated that hip flexor muscle fatigue can limit walking endurance. This pilot study used a single-blinded cross over design to investigate the effect of a 16-week home-based programme of resistance training on hip flexor muscle strength. Measures of walking endurance, gait speed, exertion, fatigue, and general activity were also recorded. The exercise protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 19 publications
1
58
0
1
Order By: Relevance
“…21 Only three randomized controlled trials were found. 9 Also in our cohort of ICU-acquired weakness, resistance training appears to be less effective to improve walking, when compared to cycle ergometer training. 9 Also in our cohort of ICU-acquired weakness, resistance training appears to be less effective to improve walking, when compared to cycle ergometer training.…”
Section: Idence-based Overview Of the Effectiveness Of Various Intervmentioning
confidence: 61%
See 1 more Smart Citation
“…21 Only three randomized controlled trials were found. 9 Also in our cohort of ICU-acquired weakness, resistance training appears to be less effective to improve walking, when compared to cycle ergometer training. 9 Also in our cohort of ICU-acquired weakness, resistance training appears to be less effective to improve walking, when compared to cycle ergometer training.…”
Section: Idence-based Overview Of the Effectiveness Of Various Intervmentioning
confidence: 61%
“…[8][9][10] During resistance training, interrupted activity at high intensity (level 16 on the Borg scale 7 ) was performed over a total of 20 minutes. A medical wheelchair ergometer training apparatus (MOTOmed, Reck, Betzenweiler, Germany) was used.…”
Section: Interventionmentioning
confidence: 99%
“…[12] Physical activity data collection took place during the control phase of the exercise trial, where participants were asked to continue with their normal routine and activities. Participants were included if they were aged 18–70 years, had a clinical diagnosis of CMT, or related condition, and were able to walk 50 meters with or without an aid.…”
Section: Methodsmentioning
confidence: 99%
“…11,12 Despite the verisimilitude of the objectives, a wide range of methods were used to measure the outcome of the evidence: muscular strength, the only common measurement, was evaluated through different methods (QMA, 1RM, myometre), so it does not allow any comparison.As for the results, all evidence points to the effectiveness of physiotherapy in CMT, as it is associated with an increase of the strength. 11–14 The muscles involved are different in different trials: the muscles of the arm, 11 the pelvic girdle and thigh (hip flexors and quadriceps), 1214 and the knee.…”
Section: Discussionmentioning
confidence: 99%